2016
DOI: 10.1002/app.44657
|View full text |Cite
|
Sign up to set email alerts
|

Role of bismuth oxide as a reinforcer on gamma shielding ability of unsaturated polyester based polymer composites

Abstract: Unsaturated Polyester resin is reinforced with Bi 2 O 3 up to 60% filler weight. The effect of bismuth oxide on gamma shielding ability of the composites is studied in terms of attenuation parameters using Ba-133, Cs-137, and Co-60 gamma ray sources. The results reveal that, the shielding property of the composite material increases with increase in the filler concentration and decreases with energy. The HVL, TVL, and relaxation length of the composites are found to decrease with increase in the filler concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(42 citation statements)
references
References 19 publications
1
40
0
1
Order By: Relevance
“…Mao et al (2015) have studied the X-ray attenuation property of rubber nanocomposite containing Gd 2 O 3 nanoflakes which is found to exhibit X-ray attenuation property and a high tensile strength. Ambika et al (2016) have studied the gamma shielding property of unsaturated polyester resin-based nanocomposite containing bismuth oxide nanoparticles, with a shielding ability comparable to that of barite at low energies of gamma rays. Scuderi et al (2006) have studied the radiation protection efficacy of commercially available non-lead-based radiation protective garments such as Xenolite, EarthSafe and Demron against X-rays of energy 60-120 keV.…”
Section: Introductionmentioning
confidence: 99%
“…Mao et al (2015) have studied the X-ray attenuation property of rubber nanocomposite containing Gd 2 O 3 nanoflakes which is found to exhibit X-ray attenuation property and a high tensile strength. Ambika et al (2016) have studied the gamma shielding property of unsaturated polyester resin-based nanocomposite containing bismuth oxide nanoparticles, with a shielding ability comparable to that of barite at low energies of gamma rays. Scuderi et al (2006) have studied the radiation protection efficacy of commercially available non-lead-based radiation protective garments such as Xenolite, EarthSafe and Demron against X-rays of energy 60-120 keV.…”
Section: Introductionmentioning
confidence: 99%
“…With different activities, ASSs are capable of chemically interacting with unbound polyester chain segments and styrene cross links. In the case of STO particles that have a higher number of ASSs as compared to TiO 2 , the particles interact more intensively with unbound polymer chain segments for C m > 1.5 % [10], and the ASS chemical bond to the chain segments leads to a reduction in I 3 (capture and annihilation of orto-positronium). It may be due to a reduction in the number of defects trapping positronium (N Ps ).…”
Section: The Positron Annihilation Lifetime Spectroscopymentioning
confidence: 99%
“…Filling of amorphous glasslike polymers (in particular, UPR) leads to restructuring of polyester and styrene chains, changing a number of unfixed fragments of macromolecule, appearance of double layers with internal electric fields. It has recently been shown that filling the UPR with either titania or silica-titania fumed oxide results in breaking the styrene cross-links and increasing a number of the unlinked moieties [10]. The dependencies of the physical parameters on filler content are characterized by a non-monotonic pattern which is clearly revealed at low filler content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• metal powders embedded in the polymeric matrices. Some of these solutions are already in commerce, e.g., tungsten-loaded polylactic acid for 3D-Printing [7]; • minerals included in polymeric matrices, typically high density oxides such as zinc oxide (ZnO), tin oxide (SnO 2 ) or bismuth oxide (Bi 2 O 3 ) [2,[8][9][10] and compounds of materials of the sixth period of the periodic table such as barium sulphate (BaSO 4 ) [11].…”
Section: Introductionmentioning
confidence: 99%